BQL Generalized Inverse Condition for Multiple Transcritical and Pitchfork Bifurcation Theorem. (25th October 2020) - Liu, Guanqi; Wang, Yuwen
Abstract: In this article, by using the bounded quasi-linear projection generalized inverse, we prove the transcritical and pitchfork bifurcation theorem for multiple eigenvalues, which is a generalized result of the famous transcritical and pitchfork bifurcation theorem for simple eigenvalue.